Review of the genus Arpedium Erichson, 1839 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini), with descriptions of five new species - Shavrin, Alexey V. (Zootaxa, 2026)
The present study provides a review of the Holarctic genus Arpedium Erichson, 1839 (Omaliinae: Anthophagini) with new taxonomic, diagnostic and bionomic data. The genus Arpedium is redescribed and illustrated, a checklist, distributional maps, and a key to species for the genus are provided, and relations with similar taxa are briefly discussed. The previously established synonymy of Eucnecosum Reitter, 1909 with Arpedium is confirmed. Three species groups of Arpedium are established for 14 species: Quadrum group containing the Holarctic A. quadrum (Gravenhorst, 1806), the Nearctic A. angulare Fauvel, 1878 (revalidated species, not synonym of A. cribratum Fauvel, 1878), A. assingi sp. nov. (China: Gansu), the Nearctic A. cribratum, A. ryvkini sp. nov. (Far Eastern Russia (Jewish Autonomous Region, Amur and Sakhalin (Kunashir Island) areas, Khabarovsk Territory and Maritime Province of Russia), Japan (Hokkaido, Honshu)) and A. schuelkei sp. nov. (China: Sichuan); Brachypterum group containing Holarctic A. brachypterum (Gravenhorst, 1802), A. brunnescens J. Sahlberg, 1871 and A. tenue (LeConte, 1863), the Palaearctic A. puncticolle J. Sahlberg, 1880, and Middle Asian A. ludgeri Assing, 2007 and A. tianshanicum sp. nov. (both from Kyrgyzstan); Schwarzi group containing A. schwarzi Fauvel, 1878 (Canada, USA) and A. thayerae sp. nov. (USA). All new species, and A. angulare, A. cribratum, and A. puncticolle are redescribed and illustrated. The aedeagus of A. puncticolle is illustrated for the first time. Arpedium columbiense Hatch, 1957 is a junior synonym of A. angulare, not synonym of A. cribratum. A new synonymy is proposed: A. brachypterum = Micralymma laticollis Motschulsky, 1860 syn. n. Lectotypes are designated for A. brunnescens and A. puncticolle. Several species are recorded for the first time: A angulare from Alberta (Canada), A. brachypterum from Karachay-Cherkessia, Kabardino-Balkaria, Tver, Perm and Amur areas, Bashkortostan, Khanty-Mansi Autonomous Region, Evenkia, Altai Republic, Tuva and Khabarovsk Territory (Russia), Kazakhstan, and Alberta (Canada), A. brunnescens from Evenkia, Altai Republic, Buryatia, Yakutia and Khabarovsk Territory (Russia), A. puncticolle from Yamalo-Nenets, Khanty-Mansi and Taimyr autonomous regions, Evenkia and Altai Republic (Russia), and Kazakhstan, A. quadrum from Bryansk, Kursk, Novgorod, Kaluga, Chelyabinsk and Orenburg areas, Adygea, North Ossetia-Alania, Evenkia, Khanty-Mansi and Taimyr autonomous regions (Russia), and Türkiye and Kazakhstan, A. schwarzi from South Dakota, Nebraska and West Virginia (USA), and A. tenue from Komi, Yamalo-Nenets and Khanty-Mansi autonomous regions, Evenkia, Tuva, Irkutsk and Chita areas, Buryatia and Khabarovsk Territory (Russia), and Idaho and Montana (USA).